(Re) construção de conhecimentos sobre cadeia alimentar : trabalhando a partir das ideias dos alunos na educação em jovens e adultos - Lindenmeyer, Clarissa Martins (2013)
This research focused on the reconstruction of science knowledge for youth and adults of Porto Alegre area in a specific elementary public school. It is analyzed how a teaching methodology built according to the student s initial ideas (Unit Learning approach) influences in learning about the Food Chain subject. Data were collected from a survey of socioeconomic profile, an initial questionnaire about previous knowledge and a final questionnaire to investigate the processes of reconstruction of knowledge. In a predominantly qualitative approach, data analysis was performed using Analysis Textual Discourse. The results show that throughout the UA approach students rebuilt their ideas on the food chain subject establishing a transition to a more complex view from everyday knowledge to scientific knowledge.